Comparison of common interventions for the treatment of infantile colic: a systematic review of reviews and guidelines. Issue 2 (25th February 2020) - Ellwood, Julie; Draper-Rodi, Jerry; Carnes, Dawn
Abstract : Objective: To conduct a systematic review of systematic reviews and national guidelines to assess the effectiveness of four treatment approaches (manual therapy, probiotics, proton pump inhibitors and simethicone) on colic symptoms including infant crying time, sleep distress and adverse events. Methods: We searched PubMed, Embase, Cochrane and Mantis for studies published between 2009 and 2019. Inclusion criteria were systematic reviews and guidelines that used evidence and expert panel opinion. Three reviewers independently selected articles by title, abstract and full paper review. Data were extracted by one reviewer and checked by a second. Selected studies were assessed for quality using modified standardised checklists by two authors. Meta-analysed data for our outcomes of interest were extracted and narrative conclusions were assessed. Results: Thirty-two studies were selected. High-level evidence showed that probiotics were most effective for reducing crying time in breastfed infants (range −25 min to −65 min over 24 hours). Manual therapies had moderate to low-quality evidence showing reduced crying time (range −33 min to −76 min per 24 hours). Simethicone had moderate to low evidence showing no benefit or negative effect. One meta-analysis did not support the use of proton pump inhibitors for reducing crying time and fussing. Three national guidelines unanimously recommended the use of education, parental reassurance, advice and guidance and clinical evaluation of mother and baby. Consensus on other advice and treatments did not exist. Conclusions: The strongest evidence for the treatment of colic was probiotics for breastfed infants, followed by weaker but favourable evidence for manual therapy indicated by crying time. Both forms of treatment carried a low risk of serious adverse events. The guidance reviewed did not reflect these findings. PROSPERO registration number: CRD42019139074.